2008
DOI: 10.1007/s00455-008-9152-5
|View full text |Cite
|
Sign up to set email alerts
|

What Information Do Clinicians Use in Recommending Oral versus Nonoral Feeding in Oropharyngeal Dysphagic Patients?

Abstract: There is little evidence regarding the type(s) of information clinicians use to make the recommendation for oral or nonoral feeding in patients with oropharyngeal dysphagia. This study represents a first step toward identifying data used by clinicians to make this recommendation and how clinical experience may affect the recommendation. Thirteen variables were considered critical in making the oral vs. nonoral decision by the 23 clinicians working in dysphagia. These variables were then used by the clinicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Using the eight main diagnostic categories used in the Chicago Classification scheme, we found ‘substantial’ agreement for the key diagnosis of achalasia and ‘fair–moderate’ agreement for classification of esophageal spasm, hypertensive, and hypotensive dysmotility for a large number of participants with a wide range of HRM experience. This performance compares well with inter‐observer agreement reported for ‘conventional manometry’ and is similar to the level of agreement documented for medical imaging in other areas of practice …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Using the eight main diagnostic categories used in the Chicago Classification scheme, we found ‘substantial’ agreement for the key diagnosis of achalasia and ‘fair–moderate’ agreement for classification of esophageal spasm, hypertensive, and hypotensive dysmotility for a large number of participants with a wide range of HRM experience. This performance compares well with inter‐observer agreement reported for ‘conventional manometry’ and is similar to the level of agreement documented for medical imaging in other areas of practice …”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that there is no consensus as to what constitutes an acceptable level of inter‐observer agreement for clinical investigations; however, comparison with similar studies performed for medical imaging (e.g. assessment of barium swallows after dysphagic stroke, tumor volume by computed tomography) and endoscopic investigations (e.g. classification of esophagitis) show similar levels of agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Cough strength has been ranked as fifth in the top 10 factors therapists use to inform their oral/nonoral recommendations. 36,37 Other oromotor parameters, when incomplete, have also been shown to be associated with increased odds for aspiration. 38 The ability to conduct valid and reliable online assessment of oromotor function has been reported previously [15][16][17][18][29][30][31]39 and is confirmed by the current data.…”
Section: Discussionmentioning
confidence: 96%
“…Determining patient safety for oral or nonoral feeding is a primary objective of the CSE. Recent research 36,37 has demonstrated that in the FTF environment, clinicians use a range of clinical information collected during a CSE to help determine patient safety for oral/nonoral IMPACT OF DYSPHAGIA SEVERITY feeding. Considering the high level of exact agreement observed between the online and FTF clinicians across all groups, the current data support prior research 15,16 that concluded that sufficient clinical information can be observed/collected via an online CSE assessment to enable accurate assessment of patient risk for oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options include pharyngeal or cervical esophageal dilatation for hypopharyngeal or esophageal strictures, crycopharyngeal muscle myotomy for upper esophageal sphincter spasm, and application of fillers to reduce glottal insufficiency or tongue base deficits (Bergamini et al 2010). Tube feeding is frequently adopted in the early phase after head and neck cancer treatment and a percentage of these patients remain on enteral feeding, even if there is not enough evidence to decide on the optimal feeding method (PEG or nasogastric tube); criteria to stop enteral feeding are mainly related to the severity of aspiration, even though there are differences in different centers (Logemann et al 2008;Nugent et al 2010).…”
mentioning
confidence: 99%